Financial Effect of Labour Related Risks on Completion of PPP Projects - Oyieyo, Pamela Akinyi; Rambo, Charles; Ndiritu, Anne (Advances in Social Sciences Research Journal, 2020)
Efficient management of construction works should focus its attention on utilizing labour, equipment, and raw materials in the right way. Besides, they claim that responsible parties should evaluate labour productivity continuously and that cost control measures should be developed. Low productivity witnessed in construction is linked to internal challenges including disputes, abandonment of projects, excess budget, and time overlaps. The objective of the study was to determine the financial effect of labour related risks on completion of PPP projects. A descriptive survey design was used with simple random sampling targeting 85 members of the management team at the completed Sondu-Miriu Power project. The participants were administered with questionnaire which were sent by mail (in some cases) and selected participants encouraged to respond. Data obtained was analysed through SPSS platform using descriptive statistics and Pearson Moment correlation as inferential statistics. The study found that labour related risks in construction PPP projects included failure by employees and experts to complete assigned tasks, injuries and deaths, changing labour demands during the project as well as cases of go slow. Construction labour related risks affected the financial cost, time and quality of work performed in the construction project. The study concludes that labour related risks have a financial effect on completion of PPP projects such that as the risks increase, the financial cost increases. The study recommends that more focus should be placed on the identification and recruitment of project staff as well task allocation.